2011
DOI: 10.1523/jneurosci.3714-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Dorsal Raphe Serotonin Neurons Underlies Waiting for Delayed Rewards

Abstract: The serotonergic system plays a key role in the control of impulsive behaviors. Forebrain serotonin depletion leads to premature actions and steepens discounting of delayed rewards. However, there has been no direct evidence for serotonin neuron activity in relation to actions for delayed rewards. Here we show that serotonin neurons increase their tonic firing while rats wait for food and water rewards and conditioned reinforcement tones. The rate of tonic firing during the delay period was significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
169
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(192 citation statements)
references
References 48 publications
23
169
0
Order By: Relevance
“…We also found that the DRN 5-HT neuronal firing increased specifically while waiting for a delayed reward at reward sites and that the increase in 5-HT neural firing ceased before the rats gave up waiting for long delayed rewards (Miyazaki et al, 2011b). The present results revealed a causal relationship between 5-HT neural activity and waiting behavior for delayed rewards.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We also found that the DRN 5-HT neuronal firing increased specifically while waiting for a delayed reward at reward sites and that the increase in 5-HT neural firing ceased before the rats gave up waiting for long delayed rewards (Miyazaki et al, 2011b). The present results revealed a causal relationship between 5-HT neural activity and waiting behavior for delayed rewards.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, we showed that serotonin efflux in the DRN increases while rats perform a task that requires waiting for a delayed reward (Miyazaki et al, 2011a). We also found that DRN serotonergic neurons increase tonic firing while rats wait for delayed rewards and cease firing before rats give up waiting for long delayed rewards (Miyazaki et al, 2011b). These results demonstrated a correlation between dorsal raphe serotonin activation and waiting behavior for delayed rewards.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…One remarkable observation from these studies is that neighboring 5-HT neurons have a high degree of diversity to respond to discrete stimuli, suggesting that 5-HT neurons are not a homogeneous population. 28,29 Our findings support this hypothesis, and confirm the existence of a subpopulation of serotonergic neurons that do not express the 5-HT1A receptor. It is difficult to speculate whether these cells correspond to any of the firing behaviors described for neurons recorded in vivo, or whether they could respond differently to external stimuli.…”
supporting
confidence: 83%
“…These results suggest that, at the stimulation patterns tested, DRN-Pet1 neurons represent a subpopulation of serotonergic neurons that promote reward behaviors in a glutamate and serotonin-dependent manner Luo et al 2015). One possibility is that increased reward learning is due to serotonin-mediated reduction in impulsivity, as previous studies found that serotonergic neurons in the DRN increase firing during a delay period before reward delivery and that optogenetic stimulation of serotonergic DRN neurons increases correct waiting behavior and performance during a delayed reward task (Miyazaki et al 2011(Miyazaki et al , 2014. When examining tonic firing within longer time scales, it was found that distinct populations of serotonergic neurons respond with higher firing rates during blocks of appetitive versus aversive trials, and vice versa (Cohen et al 2015).…”
Section: Dorsal Raphe Nuclei Projections To the Blamentioning
confidence: 83%